2012
DOI: 10.1097/mao.0b013e318259b3b1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Intratympanic Gentamicin Injection to Treat Ménière’s Disease

Abstract: A critical literature appraisal and meta-analysis shows that IT gentamicin injection can control vertigo in patients with MD who have limited hearing injury. The quality of research in this field has improved remarkably over the years. However, a large-scale randomized controlled trial is warranted to confirm the predictive factors for the effectiveness of IT gentamicin injection in treating MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 17 publications
0
33
0
3
Order By: Relevance
“…It has been delivered locally with drops or pumps. 18 The largest meta-analysis of this treatment 19 identified 599 patients in high quality trials. The study found that hearing loss had worsened in 17% of patients but that attacks of vertigo were completely abolished in 71% and 87% had substantial control.…”
Section: Medical Ablation Treatmentmentioning
confidence: 99%
“…It has been delivered locally with drops or pumps. 18 The largest meta-analysis of this treatment 19 identified 599 patients in high quality trials. The study found that hearing loss had worsened in 17% of patients but that attacks of vertigo were completely abolished in 71% and 87% had substantial control.…”
Section: Medical Ablation Treatmentmentioning
confidence: 99%
“…Aminoglycoside (AG) antibiotics such as gentamicin, neomycin, amikacin, kanamycin, tobramycin, and others are useful agents in the treatment of both serious bacterial nfections (1) and Ménière's disease (2,3). These antimicrobials are commonly used worldwide because they are less expensive than other antibiotics, and in some countries, they are less regulated by prescription-only sale.…”
mentioning
confidence: 99%
“…It has been shown that medications administered into the middle ear pass into the inner ear through oval and round windows, in very high concentrations [2] . IT gentamicin application has been widely accepted in Meniere's disease because of the dominant vestibulotoxic effect of the agent [3,4] . The mechanism of action has been supposed to be destruction of the dark cells to decrease endolymph secretion and /or vestibular sensory cells, and a reduction in the sensation of vertigo [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Some others covered the round window with connective tissue, then administered IT gentamicin [9,10] . The agent was administered together with dexamethasone in order to decrease harmful effects of the aminoglycosides [4] . It was speculated that the toxic effects of the aminoglycosides could be prevented in this way.…”
Section: Introductionmentioning
confidence: 99%